Analisis Model Pembelajaran Inquiry dalam Meningkatkan Motivasi Belajar Peserta Didik di SMP Muhammadiyah Waipare - Yuni Astuti Dewi; Yuliana Dua Solo; Dian Ernaningsih (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This study aims to determine the learning motivation of students using the inquiry learning model in class VIII B Muhammadiyah Middle School Waipare. This research was conducted from 20 March to 02 April 2023. The data sources in this study consisted of primary and secondary data. The primary data is the homeroom teacher, science teacher and class VIII B students, while the secondary data was obtained using documentation. The method used is descriptive qualitative. Data collection was obtained through observation, interviews, questionnaires and documentation. From the six indicators of motivation to learn, the following results are obtained, 1) indicators of desire and desire were successfully categorized as good with a percentage of 87,96%, 2) indicators of encouragement and need to learn are categorized as sufficient with a percentage of 75,25%, 3) indicators of hopes and aspirations are categorized as good with a percentage of 93,24%, 4) indicators of appreciation in learning are categorized as good with percentage of 90,27%, 5) indicators of a conducive learning environment are categorized as good with a percentage of 90,27%, 6) there are interesting activities categorized as good with a percentage of 78,57%. So, it can be concluded that the learning motivation of student using the inquiry learning model is categorized as good.